Wound healing complications in oncological patients: perspectives for cellular therapy - Deptuła, Milena; Zieliński, Jacek; Wardowska, Anna; Pikuła, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Various types of cancer are nowadays a serious medical and social problem and a great challenge for modern medicine. The majority of anticancer therapy is based on traditional chemotherapy and radiotherapy. Both of these highly non-specific types of treatment have a number of serious side effects including wound healing complications. Radiotherapy and chemotherapy mostly affect rapidly dividing skin cells (e.g. keratinocytes), as well as fibroblasts, melanocytes, endothelial and immune cells. Currently, there are many strategies to improve wound healing in oncological patients, including various types of dressings, biomaterials, growth factors, and cell therapies.